Effects of rumensin and bovatec on growth, feed intake, and feed efficiency in dairy calves - Isch, J. A.; Scheffel, Michael V.; Titgemeyer, Evan C.; Thomas, E. C.; Shirley, John E. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
One hundred Holstein heifers were used to examine the effects of monensin (Rumensin®) and lasalocid (Bovatec®) included in calf starter and grower diets. Heifers were assigned alternately at birth to a starter feed containing either Rumensin (28 g/ton, 90% dry matter basis) or Bovatec (40 g/ton, 90% dry matter basis). The Bovatec group was switched to a starter feed containing 28 g Bovatec/ton (90% dry matter basis) at 6 weeks of age. Both groups were switched at 8 weeks of age to grower diets designed to deliver 100 mg/head/day of either Rumensin or Bovatec. No treatment differences were observed between birth and 8 weeks of age. Heifers were moved from individual hutches at 8 weeks of age to group pens (five heifers/pen) and remained on the same treatment for the next 84 days. During this 84-day period, heifers receiving Rumensin gained more weight at a faster rate and tended to be more efficient than heifers fed Bovatec. No differences were observed in feed intake, skeletal growth as measured by hip height, or body condition score.
Keywords: Dairy; Calves; Replacement heifers; Rumensin; Bovatec